Komunikasi Simpang Siur Pada Asesmen Nasional: Kasus Literasi dan Numerasi di Tingkat Dasar - Ahmad Syaifuddin (Bajang Institute, 2022)
The weakening of interest in reading and counting students in MI/SD made the government change UN to AN. The change of policy gave rise to a confusion of information on the division of tasks in its implementation. This study aims to analyze the preparation, implementation and evaluation of national assessments in improving literacy and numeracy at the basic level. The research was carried out before and after the national assessment in the fifth grade from June to January 2021-2022. The method used is descriptive qualitative. The primary data used is the education system law number 17 of 2021 concerning the functions and objectives of national education. The secondary data is an interview with the national assessment admin of Karangrejo District, Tulungagung Regency and the teachers who carry out the national assessment in their respective schools. Samples were taken by random random sampling. The results of the study were the fear of the teachers in implementing AN because the school did not have adequate infrastructure, the confusion of the speaker in the preparation of internet data made the proctor prepare all the equipment himself when the implementation of AN was carried out and the evaluation that was not yet understood by the teachers caused a confusion of information related to the benefits of holding a national assessment.